2015
DOI: 10.1016/j.jcv.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen transcriptional profile in nasopharyngeal aspirates of children with acute respiratory tract infection

Abstract: nCounter is robust and sensitive for the simultaneous detection of viral (both RNA and DNA) and bacterial transcripts in NPA with low RNA input (<10 ng). This medium-throughput technique will increase our understanding of ARI pathogenesis and may provide an evidence-based approach for the targeted and rational use of antibiotics in pediatric ARI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Whether these approaches can work against mixed infections is a pressing question. Aspiration of bacteria from the diverse flora of the upper airway or gastrointestinal tract into the smaller airways of the lower lung can result in life-threatening bacterial pneumonias, often involving two or more bacterial species (33)(34)(35)(36). Epidemiologic studies identified a strong correlation between S. aureus colonization in the upper airway and onset of VAP, and a transition from S. aureus to P. aeruginosa as the primary pathogens in early-to late-onset VAP (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these approaches can work against mixed infections is a pressing question. Aspiration of bacteria from the diverse flora of the upper airway or gastrointestinal tract into the smaller airways of the lower lung can result in life-threatening bacterial pneumonias, often involving two or more bacterial species (33)(34)(35)(36). Epidemiologic studies identified a strong correlation between S. aureus colonization in the upper airway and onset of VAP, and a transition from S. aureus to P. aeruginosa as the primary pathogens in early-to late-onset VAP (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic reports show that nasal colonization occurs in approximately 30 to 80% of the overall population and is prevalent among children. This colonization state serves as a reservoir for invasive staphylococcal disease ( 8 , 19 , 24 35 ). In most instances, colonizing bacteria form biofilms on nasal tissue, allowing S. aureus to persist by evading host defenses and antibiotic treatment ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another prospective study investigated the nasopharyngeal microbiota in young infants with RSV infections by 16S-RNA sequencing; the authors found that RSV infection was positively associated with H. influenzae and S. pneumoniae , but negatively associated with S. aureus nasopharyngeal colonization [39]. In another study concerning nasopharyngeal aspirates from children with RSV infection aged between 6 months and 2 years, S. aureus was shown to colonize 77% of RSV-infected patients with a positive association between RSV and S. aureus nasopharyngeal carriage [40]. The conflicting data from the two latter studies may be explained by differences in target populations, sampling procedures and/or microbiological methods.…”
Section: Impact Of Viral Infections In the Respiratory Tract On Staphmentioning
confidence: 99%